2017
DOI: 10.1111/ctr.12930
|View full text |Cite
|
Sign up to set email alerts
|

Early post-transplant conversion from tacrolimus to belatacept for prolonged delayed graft function improves renal function in kidney transplant recipients

Abstract: Prolonged delayed graft function (DGF) in kidney transplant recipients imparts a risk of poor allograft function; tacrolimus may be detrimental in this setting. We conducted a retrospective single center analysis of the first 20 patients converted to belatacept for prolonged DGF as part of a clinical protocol as a novel treatment strategy to treat prolonged DGF. Prior to conversion, patients underwent an allograft biopsy to rule out rejection and confirm tubular injury. The primary outcome was the estimated gl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
26
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 31 publications
(30 citation statements)
references
References 16 publications
4
26
0
Order By: Relevance
“…Conversion to belatacept in immunologically higher risk populations, including African Americans and patients with preformed DSA, has been questioned due to the higher observed rates of BPAR with belatacept and the underrepresentation or exclusion of these patients from early phase II and III trials . In our patient cohort, we observed a rejection rate of 9.4% at 1 year following conversion to belatacept, which is in line with previous studies reporting overall rejection rates ranging from 7.0% to 16.7% for patients receiving lymphocyte‐depleting induction . While BPAR is more common following conversion to belatacept compared with CNI continuation, rejection rates are similar to those reported with conversion to mechanistic target of rapamycin (mTOR) inhibitors in the CONVERT and ASCERTAIN trials …”
Section: Discussionsupporting
confidence: 88%
See 2 more Smart Citations
“…Conversion to belatacept in immunologically higher risk populations, including African Americans and patients with preformed DSA, has been questioned due to the higher observed rates of BPAR with belatacept and the underrepresentation or exclusion of these patients from early phase II and III trials . In our patient cohort, we observed a rejection rate of 9.4% at 1 year following conversion to belatacept, which is in line with previous studies reporting overall rejection rates ranging from 7.0% to 16.7% for patients receiving lymphocyte‐depleting induction . While BPAR is more common following conversion to belatacept compared with CNI continuation, rejection rates are similar to those reported with conversion to mechanistic target of rapamycin (mTOR) inhibitors in the CONVERT and ASCERTAIN trials …”
Section: Discussionsupporting
confidence: 88%
“…The results of our experience support a strategy of early conversion to belatacept for patients with a suitable clinical indication and suggest that conversion within the first year of transplant is associated with improved renal function and 1‐year allograft survival rates >90%. Other observational studies have suggested that conversion within 3 months of transplant results in greater eGFR improvement than later conversion, and conversion within 30 days of transplant may result in even greater eGFR benefit than conversion between 61 and 90 days . This suggests a continuous relationship between the duration of CNI exposure and accumulated irreversible endothelial dysfunction and that earlier CNI avoidance by means of conversion to belatacept may result in superior effects on allograft function.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…[24][25][26] Similar to previous literature, belatacept recipients experienced higher grades of rejections, but this did not contribute to short-term graft loss, except in one patient, in whom there were adherence concerns. A few studies have previously reported the outcomes of depleting induction in conjunction with belatacept; however, these have been conducted in patients receiving more optimal quality donor kidneys.…”
Section: Discussionsupporting
confidence: 69%
“…These improvement in eGFR of about 6 mL/min. [24][25][26] Similar to previous literature, belatacept recipients experienced higher grades of rejections, but this did not contribute to short-term graft loss, except in one patient, in whom there were adherence concerns. In our study, we also combined depleting induction with steroid withdrawal.…”
Section: Evidence Of Resolving Moderate Pathologic Changes Is Encourasupporting
confidence: 69%